Revisiting Newmark’s Theory of Translation: To What Extent Is It Appropriate? - Budiman, Asep; Wulandari, Yasinta; Rosyidah, Naeli (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
In the twentieth century, when the study of cultural anthropology suggested that linguistic barriers were insuperable and that language was entirely the product of culture, the translation must be as literal as possible. This resulted in confusion among translators when translating a text, not until they were illuminated by Peter Newmark’s